2004
DOI: 10.1109/tuffc.2004.1320791
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle bombardment on the orientation and the residual stress of sputtered AlN films for SAW devices

Abstract: We present a study of the effect of particle bombardment on the preferred orientation and the residual stress of polycrystalline aluminum nitride (AlN) thin films for surface acoustic wave (SAW) applications. Films were deposited on silicon (100) substrates by radio frequency (RF) sputtering of an aluminum target in an argon and nitrogen gas mixture. The main deposition parameters were changed as follows: the total pressure from 4 mTorr to 11 mTorr, the N2 content in the gas mixture from 20% to 80%, and the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…However, several applications could make use of AlN films with such tensile stress. For example, Iborra et al [36] reported similar range of residual stress for their sputtered AlN films and successfully developed the SAW filters.…”
Section: Resultsmentioning
confidence: 99%
“…However, several applications could make use of AlN films with such tensile stress. For example, Iborra et al [36] reported similar range of residual stress for their sputtered AlN films and successfully developed the SAW filters.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is common to find grains exhibiting other orientations, in particular the (10·1), (10·2) and (10·3). The deposition conditions [7], the nature and roughness of the substrate [8], and the residual gases present in the deposition chamber [6,9] are the determining factors of crystal quality of the films, which includes the amount of misaligned grains. The dominant polarization direction finally determines the piezoelectric response of the films.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different piezoelectric materials, AlN is an interesting candidate for this integration process. Its good mechanical, chemical and dielectric properties, as well as the compatibility with CMOS technology, have determined its choice [4,5]. A number of complex techniques have been used to determine AlN piezoelectric properties, such as the piezoelectric coefficients d 33 and d 31 [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%